THE EFFECTIVENESS OF PEER TUTORING LEARNING TO IMPROVE STUDENTS’ SPEAKING ACCURACY - Adib Mahyuddin; Maemuna Muhayyang; Fauzan Hari Sudding Sally (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2026)
This study investigated the effectiveness of peer tutoring learning in enhancing students’ speaking accuracy. The main purpose was to determine whether peer tutoring learning significantly improves students’ speaking accuracy. A quantitative approach with a pre-experimental design was applied to examine the influence of peer tutoring on students’ speaking accuracy. The population comprised all second-grade students of SMPN 2 Sungguminasa, totaling 120 learners, from which 42 students were chosen as the sample. A speaking test was utilized as the research instrument. The findings indicated that peer tutoring learning was highly effective in improving students’ speaking accuracy, as demonstrated by the T-test result with a significance value of 0.000, which was lower than 0.05. Therefore, the alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. The results also showed a substantial improvement in students’ scores from the pre-test to the post-test, especially in the aspects of pronunciation, vocabulary, and grammar. It can be concluded that peer tutoring learning is effective in improving students’ speaking accuracy.Keywords:  peer tutoring, speaking, accuracy